(untitled) - Sutcliffe, William (London, 2000)
What happens to friends and lovers when sex gets in the way? Six twentysomethings confront their feelings, and each other, in their quest for happy-ever-after romance
Keywords: Triangles (Interpersonal relations),Love stories,Quan hệ tay ba; Tiểu thuyết